Pengaruh Social Media Marketing Activities dan Brand Image Terhadap Purchase Intention di Hotel ZHM Premiere Padang - Florensia, Wiva Audi; Abrian, Youmil; Fansurya, Alfi Husni (Universitas Dharma Andalas, 2024)
In the historical of digitalization and technological advancements, hotel industry Using social networking as their main advertising medium services to potential customers. In response to the increasingly competitive marketing landscape on social media, particularly in terms of hotel promotions in Padang City, this study was conducted by ZHM Premiere Padang Hotel. The aim of this study was to explore the impacts of the most recent trends in hotel marketing in Padang City on capturing customer attention, enhancing hotel visibility, and influencing customer purchase intentions. The research population consisted of social media users who follow and have engaged with the social media activities of Hotel ZHM Premiere Padang, with a total of 120 sample. Multiple linear regression was employed for hypothesis testing, and the conclusions demonstrated that the use of social media for marketing (X1) have a noteworthy enhancement of purchase intention (Y). Additionally, brand image (X2) was discovered to significantly positively impact purchasing intention (Y). Furthermore, the study demonstrated that both and purchase intention intention was significantly influenced by brand image and social media marketing activities. Abstark Dalam era digital dan kemajuan teknologi, industri perhotelan memanfaatkan media sosial media menjadi salah satu cara utama memperkenalkan produk atau jasa mereka kepada calon konsumen, platform tersebut menjadi sangat penting. Sebagai respon penelitian ini dilakukan di Hotel ZHM Premiere Padang terhadap fenomena persaingan pemasaran yang semakin ketat di media social, khususnya dalam hal promosi hotel di Kota Padang. Penelitian ini dilakukan untuk melihat pengaruh tren terbaru dalam pemasaran hotel di Kota Padang untuk menarik perhatian pelanggan, meningkatkan visibilitas hotel, dan memengaruhi niat pembelian pelanggan. Jumlah sampel dalam populasi penelitian ini adalah 120 pengguna media sosial yang mengikuti dan pernah melihat aktivitas Hotel ZHM Premiere Padang. Pengujian hipotesis menggunakan regresi linear berganda dan didapatkan hasil social media marketing activities(X1) Memberikan dampak positif yang signifikan atas purchase intention (Y), brand image (X2) memberikan dampak positif yang signifikan atas purchase intention (Y) dan social media marketing activities dan brand image memiliki dampak bersama-sama atas purchase intention.